SISTEM INFORMASI PERPUSTAKAAN DI SMP SWASTA GKPI PADANG BULAN MEDAN BERBASIS WEB - Br. Siagian, Rut Magdalena; Siringoringo, Rimbun; Simamora, Roni J. (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2023)
Information systems are needed in libraries to support the knowledge, understanding and information of students and teachers in schools to support teaching and learning processes in schools. This information is data that is processed in a form that is more useful and meaningful to the people who receive it. One of the things that can affect the school's operational mission is the design and creation of a web information system for the GKPI Padang Bulan Medan Private School Library. Information that is not timely, inaccurate and inefficient can be overcome by implementing this system, the library is very important to assist the implementation of data management and transactions that occur in the library. The library is an organizational entity that functions as a container for collecting, storing, managing, and managing in a structured manner various kinds of library materials. These materials are designed to be accessible and utilized by users as sources of information, references, or information research materials as well as learning and playing tools. The author aims to facilitate the process of borrowing books by utilizing a system that is run via a computer so that if you are not careful it can disrupt the normal operation of the library and can be repaired